Effect of Cadmium And Copper on the Growth of Pleurotus ostreatus - Tan, Shu Rong (2017)
Recently, heavy metals pollution has become a global issue. Many studies showed that heavy metal at high concentrations could result in toxicity in living organisms. Heavy metals such as cadmium (Cd), arsenic (As), mercury (Hg) and lead (Pb) cause toxicity even at low concentration. Mycoremediation could be the solution for heavy metal contamination in the environment. Pleurotus ostreatus is a good candidate to remove heavy metal because it has high viability, high tolerance towards temperature and high adsorption towards heavy metal. The objective of this study was to determine the effect of cadmium (Cd) and copper (Cu) towards the growth of P. ostreatus. In this experiment, the spawn of P. ostreatus was cultured on the centre of the potato dextrose agar (PDA) medium and PDA media supplemented with nine different concentrations of Cd or Cu (1, 5, 10, 20, 50, 100, 150, 200, 400 mg/L). In this study, the optimum growth of P. ostreatus in PDA media containing Cd was achieved at 1 mg/L Cd whereas the lowest growth was produced at 400 mg/L with the mean of radius as 4.38 cm and 0.88 cm, respectively. On the other hand, PDA medium supplemented with 5 mg/L Cu produced the optimum mycelial growth while 400 mg/L Cu showed the lowest mean of mycelial radius. It was noticed that Cd exerted higher toxicity at elevated concentrations towards P. ostreatus than Cu. Pleurotus ostreatus is tolerant to certain level of heavy metals and could serve as an agent of mycoremediation.